The Forecasting of Regional Social and Economic Development - Nizhegorodtsev, Robert Mikhaylovich; Piskun, Elena Ivanovna; Kudrevich, Viktoriya Vladimirovna (Economy of Regions, 2017)
At present, the Russian economic situation is characterized by significant imbalances in regional development. So, the forecasting of the indexes of regional social and economic development has become especially relevant. The authors offer a technique of the forecasting of regional social and economic development, it consists of two blocks. The first one is the estimation and forecasting of the level of regional social and economic development. For the purposes of this block, we applied a method of development level and some adaptive methods. The informative basis is the data on the social and economic development of the Republic of Crimea. The change of the integrated index’s growth rate, which is used for the inertial and realistic scenarios, defined the conclusions on the regional socio-economic development. The second block of this technique includes the estimation and forecasting of the social and economic state of considered region. This block is based on the methods of cluster, discriminate and adaptive analyses. The information basis is the data of the social and economic situation of 79 Russian regions for the last 14 years. On the basis of cluster analysis, we divide all Russian regions into two clusters according to their social and economic position. Discriminate models allowed to determine the prospective rate of the Republic of Crimea. The adaptive methods made possible the identification of the researched region to a certain cluster. In the article, the presented models support a complex estimation of the level of regional socio-economic development in the current forecast period and can be considered as a tool of decision-making support at the multivariate scenario analysis of the regional development strategy.